Single-molecule Studies of Proteins - Oberhauser, Andres F.; Oberhauser, Andres F. (Biophysics for the Life Sciences ;, 2013)
Single-molecule measurement techniques are providing fundamental information on the structure and function of biomolecules and are becoming an indispensable tool to understand how proteins work. During the last two decades, this field has grown at an almost exponential rate in terms of biological and biophysical applications. Single-molecule techniques have opened new fields of science that are at the crossroads of several disciplines such as biology, physics, chemistry, material science and computer science. These methods are often the approach of choice to clarify and better understand the structure and function of single proteins. This volume consists of up-to-date and comprehensive reviews of important and timely applications of different biological problems tackled by single-molecule methods; it also covers basic principles of operation, experiment and theory. In Single-molecule Studies of Proteins, expert researchers discuss the successful application of single-molecule techniques to a wide range of biological events, such as the imaging and mapping of cell surface receptors, the analysis of the unfolding and folding pathways of single proteins, the analysis interaction forces between biomolecules, the study of enzyme catalysis or the visualization of molecular motors in action. The chapters are aimed at established investigators and post-doctoral researchers in the life sciences wanting to pursue research in the various areas in which single-molecule approaches are important; this volume also remains accessible to advanced graduate students seeking similar research goals.